Exploration of efficacy and bleeding with combined phosphoinositide 3‐kinase β inhibition and aspirin in man - Nylander, S.; Wågberg, F.; Andersson, M.; Skärby, T.; Gustafsson, D. (Journal of thrombosis and haemostasis, 2015)
Summary Background Based on animal and human data, phosphoinositide 3‐kinase (PI3K)β is a promising antithrombotic target. However, the relation between efficacy and bleeding when combined with current antiplatelet therapies is unclear. Objective To strengthen the PI3Kβ target validation using the short‐acting inhibitor AZD6482 alone and in different combinations with P2Y12 and cyclooxygenase (COX)‐1 inhibition in vitro (human platelets), in vivo (dog), and in healthy subjects. Methods and Results Evaluation of complete target inhibition of PI3Kβ (by AZD6482), P2Y12 (by ticagrelor), and COX‐1 (by aspirin) alone and in the different combinations vs. concentration responses for a panel of platelet agonists in vitro (adenosine diphosphate, collagen, thrombin receptor activating peptide) indicates that the rank order of antiplatelet efficacy is P2Y12 > PI3Kβ > COX‐1 as monotherapy and P2Y12 plus PI3Kβ > P2Y12 plus COX‐1 > PI3Kβ plus COX‐1 as dual therapy, with little additional effect with triple therapy. Use of a conscious dog model to assess ex vivo antiplatelet effect in parallel with bleeding time prolongation (standard incision in the ear) confirms the wide separation of efficacy vs. bleeding for PI3Kβ inhibition and that this separation is reduced when combined with aspirin and more reduced when combined with clopidogrel. In healthy subjects, AZD6482, in combination with aspirin, shows a potential for greater antiplatelet potency but less bleeding potential compared with clopidogrel plus aspirin. Conclusions PI3Kβ inhibition, in comparison with P2Y12 and COX‐1, delivers medium antiplatelet effect but with minimal bleeding. PI3Kβ inhibition, in combination with aspirin, in healthy subjects, provides a potential for greater overall antiplatelet effect compared with clopidogrel plus aspirin, but with significantly less bleeding potential.